Characteristics of traumatic brain injury in children and adolescents hospitalized in a Brazilian trauma reference center: a retrospective cross-sectional study - José Roberto Tude Melo; Caio Vinicius de Almeida Chaves; Cindy Kawano; Maria Antonia Coladeti Fernandes; Reem Hussin; Jean Gonçalves de Oliveira; José Carlos Esteves Veiga (Arquivos de Neuro-Psiquiatria)
Background Approximately 20% of victims of traumatic brain injury (TBI) in Brazil are children and adolescents, with more than 900 deaths per year.